MANAJEMEN DIARE PADA ANAK OLEH PERAWAT DI RUMAH SAKIT - Septi Wardani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2016)
Objective: the aim of this study is to explore how the nurse’s role in management of acute diarrhea for children. Methods: this study used qualitative method with case study approach. Subject of this study is the nurse whose match with several inclusion criterias, i.e nurse whose exposed in nursing care implementation on children with acute diarrhea, had minimum of diploma degree and minimum one year working time. The data was collected by interview, documentation, and participatiory observation, and analyzed using Miles and Huberman model, and further triangulation is done in the validity. Results: there are strength and weakness for management of diare from the nurses. The strength i.e Nurse’s are doing a general assessment of diarrhea and dehydration, Nurse’s perform formulation nursing diagnosis, intervention, implementation and evaluation, Nurse’s colaboration with other health team, such as doctor, laboratory worker, Nurse’s provide education in the provision of oral rehydration, zinc, eating and education and Nurses perform the role as protector: informed concent. The weakness i.e Nurse documentation contained in separate nursing assessment form, There was incorrect of examination for severe dehydration, Child always gets additional parenteral fluid, Nuse still gave antibiotics for children with acute diarrhea, Child was given a prebiotic, Nurses did not give an explanation to the parents about the duration of zinc and Nurses doing informed concent but not yet documented. Conclusion: The nurses have been working on roles in acute diarrhea management for children, in which these roles there are strength and weakness of the implementation of those roles.